Dimethylsphingosine Regulates Intracellular pH and Ca2+ Human Monocytes - Eun-Hee Lee; Yun-Kyung Lee; Young-Jin Im; Jae-Ho Kim; Fumikazu Okajima; Dong-Soon Im (Elsevier, 2006)
Abstract.: Dimethylsphingosine (DMS) was first reported as an inhibitor of protein kinase C and later has been used as a specific inhibitor of sphingosine kinase. Furthermore, its anti-cancer effect has become a basis for development of chemotherapy. Nevertheless, its anti-neoplastic mechanism has poorly been understood. In the present study, we observed that DMS increased intracellular pH and Ca2+ concentration in U937 human monocytes. To further characterize these DMS-induced actions, we employed structurally-related sphingolipids and specific pharmacological tools such as inhibitors of protein kinase C and Na+/H+ exchanger and found that the two responses of DMS were mimicked by four stereoisomers of sphingosine and two isomers to dihydrosphingosine, but not with sphingosine 1-phosphate, sphingosyl-phosphorylcholine, and C2-ceramide. Furthermore, DMS-induced pH increase was independent of Na+/H+ exchanger activity. We also characterized the interrelationship between DMS-induced pH increase and DMS-induced Ca2+ increase. Since DMS is considered to be a good anti-cancer candidate, our characterization of DMS actions provides useful information for development of DMS chemotherapy. Keywords:: dimethylsphingosine, pH, sphingosine, calcium, signal transduction